2021
DOI: 10.7150/ijms.51735
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Exosomes derived from the Aqueous Humor of Myopia Patients

Abstract: Objectives: Myopia is the most common refractive vision disorder. In recent years, several studies have suggested that the alteration of the exosomal protein levels in the aqueous humor (AH) is associated with the development of several eye diseases. Therefore, we aimed to explore the exosomal protein profile of the AH from myopia patients. Methods: Exosomes were isolated from the AH. The quality, concentration, and size distribution of exosomes for each patient were measured using nanoparticle tracking analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Lines of evidence suggest abundant exosomes are common in AH [15,16]. Recent research has linked exosomal proteins or miRNAs to variety of ophthalmic diseases [17][18][19][20]. To examine the changes of exosomal proteins that occur with the development of AMD, we aimed to compare the individual protein profiles from patients with AMD, using liquid chromatography-tandem mass spectrometry (LC-MS/MS).…”
Section: Introductionmentioning
confidence: 99%
“…Lines of evidence suggest abundant exosomes are common in AH [15,16]. Recent research has linked exosomal proteins or miRNAs to variety of ophthalmic diseases [17][18][19][20]. To examine the changes of exosomal proteins that occur with the development of AMD, we aimed to compare the individual protein profiles from patients with AMD, using liquid chromatography-tandem mass spectrometry (LC-MS/MS).…”
Section: Introductionmentioning
confidence: 99%
“…4 MicroRNAs and proteins in aqueous humor exosomes differentiate between patients with high myopia and non-myopia. 5 , 6 It has been reported that exosomes secreted by mesenchymal stem cells and neural progenitor cells can protect retinal photoreceptors and combat retinal degeneration through a variety of microRNA. 7 , 8 In this way, exosomal microRNAs may play an important role in myopic maculopathy.…”
mentioning
confidence: 99%
“…Accordingly, we enrolled 3 groups, including the non-MM, MAM, and pmCNV groups, for proteomic testing. Several studies have investigated alterations in AH protein expression in human samples in myopic populations through high-throughput techniques [ 14 , 15 ], but few have strictly classified the different types of MM depending on the practical and newest category—the ATN grading system [ 12 , 24 ].…”
Section: Discussionmentioning
confidence: 99%